Method for producing composite material and composite material

A composite material made from Sr and Ce compounds, calcined at 800-1300°C, addresses the inefficiencies and environmental concerns of existing electrode material manufacturing methods by achieving low activation energy and reduced electrode resistance in solid oxide fuel cells.

JP7658171B2Active Publication Date: 2025-04-08SAKAI CHEM IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021087052
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-16
Filing Date
2021-05-24
Publication Date
2025-04-08
Estimated Expiration
2041-05-24

AI Technical Summary

Technical Problem

Existing methods for manufacturing electrode materials for solid oxide fuel cells are inefficient, requiring special equipment and generating nitrogen oxides, which are environmentally harmful. Additionally, these materials exhibit high activation energy, leading to increased electrode resistance at low temperatures.

Method used

A composite material is developed using a mixture of electron-conductive and ionic conductive materials, specifically Sr-containing and Ce-containing compounds, which are calcined at 800-1300°C to produce a material with low activation energy for electrode reactions. This method does not require special equipment and minimizes environmental impact.

Benefits of technology

The composite material achieves low activation energy for electrode reactions, reducing electrode resistance across a wide temperature range, making it suitable for solid oxide fuel cells with lower operating temperatures and improved handling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658171000002
    Figure 0007658171000002
  • Figure 0007658171000003
    Figure 0007658171000003
  • Figure 0007658171000004
    Figure 0007658171000004
Patent Text Reader

Abstract

To provide a method of manufacturing a material that makes it possible to form an electrode with small activation energy of the electrode reaction obtained from an electrical resistance value in a wide temperature range when used as an electrode of a fuel cell with a simple way without a high load on the environment.SOLUTION: A manufacturing method of a composite material of an electromagnetic material represented by the formula of X1-pSrpCoO3-δ (1). (X represents at least one element selected from La, Sm, and Gd, and 0<p<1 is satisfied. δ represents the amount of oxygen deficiency) and an ionic conductive material represented by the formula of Ce1-qAqO2-q / 2 (2). (A represents at least one element selected from La, Sm, and Gd, and 0<q<1) includes a mixing step of mixing a raw material containing a compound containing a metal element constituting an electron conductive material and an ionic conductive material to obtain a raw material mixture, and a step of introducing the raw material mixture into a heating device and firing at 800 to 1300°C, and a Sr-containing compound contained in the raw material is a carbonate, and at least one of the compounds containing a metal element other than Sr is a carbonate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a composite material and a composite material. [Background technology]

[0002] Fuel cells are devices that generate electricity by electrochemically reacting fuels such as hydrogen or alcohol with oxygen. Fuel cells are classified into various types depending on the electrolyte, operating temperature, etc., including polymer electrolyte fuel cells (PEFCs), phosphoric acid fuel cells (PAFCs), molten carbonate fuel cells (MCFCs), and solid oxide fuel cells (SOFCs).

[0003] Of these fuel cells, solid oxide fuel cells (SOFCs) are fuel cells in which the air electrode (cathode), fuel electrode (negative electrode), and electrolyte are all made of solid materials, and are characterized by high power generation efficiency, the ability to use not only hydrogen but also methane and carbon monoxide as fuel, and a simple structure that makes them easy to miniaturize and reduce costs. SOFCs usually have a high operating temperature of 800 to 1000°C, which is one of the reasons why they have high power generation efficiency, but at the same time, there is a demand for lower operating temperatures to make them easier to handle. In order to lower the operating temperature of SOFCs, it is important to use an electrode material that has low electrode resistance even at low temperatures, and such an electrode material is required. In this regard, a composite particle powder in which an electronic conductive material and an ion conductive material are aggregated, and which has a predetermined particle size distribution and BET specific surface area, has been proposed as an electrode material with low electrode resistance (see Patent Document 1). In addition, such composite particle powders can be used as electrodes for SOFC reverse reaction electrolysis cells (SOECs). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 084279 Summary of the Invention [Problem to be solved by the invention]

[0005] For the solid oxide fuel cell, which has various advantages as described above, to be more widely used, it is required to lower the operating temperature and improve it to be easier to handle, and there is a demand for the development of an electrode material that makes this possible. The material of Patent Document 1 is one such electrode material, but in Patent Document 1, the electrode material is manufactured using a spray pyrolysis method that requires special equipment. This method is not suitable for mass production because it takes a long time for mass production. In addition, the method of Patent Document 1 uses nitrates as raw materials, and nitrogen oxides are generated during the production of the electrode material, which has a high environmental impact. For the wider use of solid oxide fuel cells, it is important that the electrode material can be mass-produced in a simpler and less environmentally impactful manner, and there is a demand for the development of such a manufacturing method. In addition, the electrode materials used in solid oxide fuel cells have a problem in that the activation energy of the electrode reaction calculated from the electrical resistance value over a wide temperature range is high. When the activation energy is high, the electrode resistance increases rapidly at low temperatures. In detail, even if the electrode resistance is low at high temperatures above 800°C, the electrode resistance increases rapidly at low temperatures below 800°C. For this reason, the operating temperature of conventional solid oxide fuel cells had to be increased. In order to lower the operating temperature of solid oxide fuel cells and improve them to make them easier to handle, it is necessary to develop electrode materials that have a small increase in resistance value over a wide temperature range from high temperatures to low temperatures below 800°C, that is, electrode materials that have a small activation energy of the electrode reaction calculated from the electrical resistance value over a wide temperature range.

[0006] In view of the above-mentioned current situation, the present invention aims to provide a method for producing a material that makes it possible to form an electrode having a small activation energy for the electrode reaction determined from the electrical resistance value over a wide temperature range when used as an electrode for a fuel cell, in a simple manner and without imposing a heavy burden on the environment. [Means for solving the problem]

[0007] The inventors of the present invention studied a method for manufacturing a material that can be used as an electrode of a fuel cell with a small activation energy of an electrode reaction obtained from an electrode resistance value in a wide temperature range, simply and without imposing a high environmental load. They focused on a composite material of a predetermined electron-conductive material containing Sr element and a predetermined ion-conductive material containing Ce element. Then, when a predetermined compound is used as a compound containing metal elements as these raw materials, and after mixing these raw materials, firing is performed at a predetermined temperature, it has been found that it is possible to manufacture a composite material capable of forming an electrode with a small activation energy of an electrode reaction simply and without imposing a high environmental load. Furthermore, the inventors found that the microscopic composite state of the composite material greatly affects the activation energy of the electrode reaction obtained from the electrical resistance value in a wide temperature range, and contrary to the previous prediction that a composite state in which the electron-conductive material is connected is better from the viewpoint of conductivity, it was found that a larger number of independent particles of the electron-conductive material is better. They also found a composite state material capable of forming an electrode with a low activation energy of the electrode reaction obtained from the electrode resistance value in a wide temperature range, and thus completed the present invention.

[0008] That is, the present invention relates to the following formula (1); X 1-p Sr p CoO 3-δ (1) (In the formula, X represents at least one element selected from La, Sm, and Gd, and 0 < p < 1. δ represents the amount of oxygen deficiency.) an electron-conductive material represented by the following formula (2); Ce 1-q A q O 2-q / 2 (2) (In the formula, A represents at least one element selected from La, Sm, and Gd, and 0 < q < 1.) A method for producing a composite material with an ion conductive material, the production method comprising: a mixing step of mixing a raw material containing a compound containing a metal element constituting an electron conductive material and an ion conductive material to obtain a raw material mixture; and a step of introducing the raw material mixture into a heating device and firing at 800 to 1300 °C, wherein the Sr-containing compound contained in the raw material is a carbonate, and at least one of the compounds containing a metal element other than Sr is a carbonate. This is a method for producing a composite material characterized by this.)

[0009] In the above production method, it is preferable that the Co-containing compound among the compounds containing a metal element other than Sr is a carbonate.

[0010] The above mixing step is preferably a step of mixing a raw material containing at least one carbonate in a compound containing a metal element other than Sr in a powder or slurry state.

[0011] The above mixing step is also preferably a step of dissolving and mixing a raw material containing at least a carbonate containing the X element in formula (1) or the A element in formula (2) and a carbonate containing Ce or Co in a solvent.

[0012] The present invention also provides the following formula (1); X 1-p Sr p CoO 3-δ (1) (In the formula, X represents at least one element selected from La, Sm, and Gd, and 0 < p < 1. δ represents the amount of oxygen deficiency.) An electron conductive material represented by the following formula (2); Ce 1-q A q O 2-q / 2 (2) (In the formula, A represents at least one element selected from La, Sm, and Gd, and 0 < q < 1.) A composite material with an ion conductive material, wherein the composite material is press-molded and fired to obtain a density of 4.5 to 6.5 g / cm 3The composite material is also characterized in that, in a 4.5 μm × 6.0 μm field of view obtained by photographing a cross section of the sintered body of the above-mentioned composition using an electron microscope, the ratio of the length of the interface where the electron conductive material particles and the ion conductive material particles are in contact with each other to the number of electron conductive material particles (interface length / number of electron conductive material particles) measured by the method described below is greater than 0 μm and less than 13 μm. <Method for measuring the length of the interface between particles of electronic conductive material and particles of ion conductive material> The backscattered electron image of the cross section of the sintered body is divided into an ion conductive material phase, an electronic conductive material phase, and a vacancy phase by binarization according to a specified brightness range, and the perimeter of each phase is calculated according to the following formula. (Interface length between electronic conductive material phase and ionic conductive material phase) = (Perimeter length of electronic conductive material phase + Perimeter length of ionic conductive material phase - Perimeter length of vacancy phase) / 2 <Method for measuring the number of electron conductive material particles> A closed region in the binarized region after the binarization process is regarded as one particle, and the number of all the closed regions is regarded as the number of electron conductive material particles.

[0013] In the above composite material, the ratio of the number of electron conductive material particles to the total number of electron conductive material particles and ion conductive material particles is preferably 10% or more.

[0014] The present invention also relates to an electrode for a fuel cell, which is characterized by using the composite material of the present invention. Effect of the Invention

[0015] The method for producing a composite material of the present invention is a method that enables a composite material that can be used as an electrode for a solid oxide fuel cell to be produced simply and without using any special production equipment and without placing a heavy burden on the environment, and is a useful production method that can also be used for the industrial production of composite materials. Furthermore, the composite material of the present invention is a composite material capable of forming an electrode having a low activation energy of the electrode reaction determined from the electrode resistance value over a wide temperature range. [Brief description of the drawings]

[0016] [Figure 1] It is a figure showing histograms before and after quantization in the luminance quantization step of image analysis for confirming the value of (length of interface / number of particles of electron conductive material) of the sintered body of the composite material manufactured in Example 1. [Diagram 2] It is a figure showing the luminance value, frequency, first peak ratio on the low luminance side, area ratio of the electron conductive material phase to the total area of the electron conductive material phase and the ion conductive material phase, and the boundaries of the pore phase, the electron conductive material phase, and the ion conductive material phase obtained in the image analysis for confirming the value of (length of interface / number of particles of electron conductive material) of the sintered body of the composite material manufactured in Example 1. [Diagram 3] It is a figure showing images at each stage of the image analysis for confirming the value of (length of interface / number of particles of electron conductive material) of the sintered body of the composite material manufactured in Example 1. [Figure 4] It is a figure showing an enlarged image of the upper left region of the image at each stage of FIG. 3. [Diagram 5] It is a figure showing the correlation between the activation energy of the electrode reaction of the composite materials manufactured in Examples 1 to 6 and Comparative Example 1 and the value of (length of interface / number of particles of electron conductive material).

BEST MODE FOR CARRYING OUT THE INVENTION

[0017] Hereinafter, preferred embodiments of the present invention will be specifically described. However, the present invention is not limited only to the following description, and can be appropriately changed and applied without changing the gist of the present invention.

[0018] 1. Method for manufacturing composite material The method for manufacturing the composite material of the present invention is represented by the following formula (1); X 1-p Sr p CoO 3-δ (1) (In the formula, X represents at least one element selected from La, Sm, and Gd, and 0 < p < 1. δ represents the amount of oxygen deficiency.) and the following formula (2); Ce 1-q A q O 2-q / 2(2) (In the formula, A represents at least one element selected from La, Sm, and Gd, and 0 < q < 1.) A mixing step of mixing raw materials containing a compound containing a metal element constituting an ion conductive material represented by the formula, to obtain a raw material mixture, and a step of firing the raw material mixture at 800 to 1300°C are included. The Sr-containing compound contained in the raw materials is a carbonate, and at least one of the compounds containing a metal element other than Sr is a carbonate. The compound (compound serving as a metal element source) containing the metal elements constituting the electron conductive material represented by the above formula (1) and the ion conductive material represented by the above formula (2) is a compound containing the X element of the above formula (1), an Sr-containing compound, a Co-containing compound, a Ce-containing compound, and a compound containing the A element of the above formula (2). In the production method of the present invention, a compound containing only one type of each of these metal elements may be used as a raw material, or a compound containing two or more types of these metal elements may be used. In the present invention, the electron conductive material means a material having catalytic activity for the oxidation or reduction reaction of the air electrode side gas and having the property of conducting electrons, and the ion conductive material means a material having the property of conducting ions oxidized or reduced at the air electrode.

[0019] In the above formula (1), p is a number in the range of 0 < p < 1, but in order to exhibit high electron conductivity, it is preferably 0.3 < p < 1. In order to be compatible with chemical stability, more preferably, 0.3 < p < 0.6. In the above formula (2), q is a number in the range of 0 < q < 1, but from the viewpoint of suppressing the generation of a heterogeneous phase, it is preferably 0 < q < 0.5. In order to exhibit high ion conductivity, more preferably, 0.05 < q < 0.3. In the above formula (1), δ represents the amount of oxygen deficiency, and takes different values depending on the composition, temperature, atmosphere, etc., but is a value in the range of 0 to 1.

[0020] The Sr-containing compound used as a raw material in the production method of the present invention is a carbonate, and at least one of the compounds containing a metal element other than Sr is a carbonate. Among the compounds containing a metal element other than Sr, any of the compounds of the metal elements X in the above formula (1), Co, Ce, and A in the above formula (2) may be carbonates. In addition, only a compound of one of these metal elements may be a carbonate, or compounds of two or more metal elements may be carbonates.

[0021] In the mixing step in the production method of the present invention, an organic acid may be added. Examples of the organic acid include acetic acid, oxalic acid, citric acid, malic acid, etc., and one or more of these may be used. When an organic acid is added, an organic acid salt of a metal element is generated in the raw material mixture, and therefore, in the production method of the present invention, the raw material may contain an organic acid salt of a metal element. When the compound of the metal element used as a raw material in the production method of the present invention contains a compound other than a carbonate or an organic acid salt, examples of the compound include an oxide, a hydroxide, and the like.

[0022] The raw material may contain a compound that is a source of metal elements constituting the electron conductive material represented by the formula (1) and the ion conductive material represented by the formula (2). From the viewpoint of suppressing the generation of a different phase, the content of the Co-containing compound contained in the raw material is preferably such that the total amount of Sr element contained in the Sr-containing compound and X element contained in the X-containing compound is 0.9 to 1.1 mol per 1 mol of Co element contained in the Co-containing compound, more preferably 0.93 to 1.07 mol, and even more preferably 0.96 to 1.04 mol.

[0023] In the production method of the present invention, the ratio of each metal element contained in the produced composite material is approximately the same as the ratio of each metal element contained in the raw materials, so the ratio of compounds of each metal element other than the Co-containing compound contained in the raw materials may be adjusted so that the ratio of each metal element contained in those compounds is the same as the ratio of each metal element contained in the desired composite material.

[0024] The mixing step of mixing raw materials including a compound containing a metal element constituting the above-mentioned electron conductive material and ion conductive material to obtain a raw material mixture is not particularly limited in the mixing method as long as the raw material compounds are sufficiently mixed, and the raw material compounds may be mixed in a powder or slurry state (solid phase method), or the raw material compounds may be mixed in a solution dissolved in a solvent (liquid phase method).

[0025] When the raw material compounds are mixed in a powder or slurry state (solid phase method), the mixing method is not particularly limited, and a ribbon mixer, Spartan mixer, Super mixer, V blender, Henschel mixer, sample mill, planetary ball mill, bead mill, vibration mill, media-less grinder, etc. can be used. When using any of the planetary ball mill, bead mill, and vibration mill, examples of the media to be used include glass beads, alumina beads, zirconia beads, titania beads, silicon nitride beads, agate beads, and tungsten carbide beads. The media used preferably has a diameter of 0.1 to 5 mm. The mixing time varies greatly depending on the equipment used, but is usually within the range of 30 to 500 minutes and may be adjusted appropriately depending on the equipment used.

[0026] When adding a solvent to the raw material compounds and wet-mixing them in a slurry state, the amount of the solvent to be used is not particularly limited, but is preferably 50-200% by mass relative to 100% by mass of the total of the compounds containing metal elements contained in the raw materials. In this concentration range, the viscosity of the slurry is within a suitable range and the raw material concentration is not too low, which is excellent in terms of raw material mixing efficiency and production cost. Examples of the solvent to be used when adding and mixing a solvent include water, an aqueous solution of the above-mentioned organic acid, an organic solvent, etc., and one or more of these can be used. Among these, water is preferred as the solvent from the viewpoint of production costs.

[0027] When a compound containing a metal element other than Sr is mixed in a powder or slurry state with a raw material compound containing at least one carbonate, the ratio of the length of the interface where the electron conductive material particles and the ion conductive material particles are in contact with each other to the number of electron conductive material particles (interface length / number of electron conductive material particles) tends to be small, as described later. In this case, a carbonate of any metal element other than Sr may be used, but it is preferable to use a carbonate of either a metal element of Ce or Co. It is more preferable to use a carbonate of Co. The composite material of the present invention, which has a low activation energy determined from the measurement results of electrical resistance over a wide temperature range as described below, has a large number of particles of electronic conductive material when viewed microscopically. Such a material can be produced by using carbonate as the raw material of the electronic conductive material, particularly by using Sr as a carbonate, and it is further preferable to use carbonate as the raw material for Co, which accounts for about half the number of moles of the metal elements constituting the electronic conductive material. By producing a composite material using such a production method, a composite material having a larger number of particles of the electron conductive material, i.e., a finer electron conductive material, can be obtained. Therefore, even when the obtained composite material is press-molded and sintered to produce a sintered body, the desired microscopic composite state, in which the number of independent particles of the electron conductive material is large, can be maintained, and the composite material can be suitably used as an electrode.

[0028] The raw material mixture after the mixing step preferably has a median particle size distribution (hereinafter, D50) of 0.05 to 1 μm. Such a particle size allows the firing temperature to be lowered in order to obtain a single-phase composite material of the electronic conductive material represented by formula (1) and the ion conductive material represented by formula (2). D50 is more preferably 0.05 to 0.15 μm, further preferably 0.05 to 0.12 μm, and particularly preferably 0.05 to 0.11 μm. The raw material mixture refers to a slurry after the raw materials are mixed or a dried powder of the slurry. The D50 of the raw material mixture can be measured by the method described in the Examples below.

[0029] In the case where the raw material compounds are dissolved in a solvent and mixed in the form of a solution (liquid phase method), the solvent to be used is not particularly limited as long as the raw material compounds are soluble in the solvent, and one or more of water, an aqueous solution of the organic acid described above, an acidic solvent, an organic solvent, and the like can be used.

[0030] When the raw material compounds are dissolved in a solvent to prepare a solution and mixed, it is preferable to use raw materials containing at least a carbonate containing the X element in formula (1) or the A element in formula (2) and a carbonate containing Ce or Co. This makes it possible to obtain a material in which the electronic conductive material represented by formula (1) and the ion conductive material represented by formula (2) are finely composited. It is more preferable to use carbonates as all of the metal element sources.

[0031] When the mixing step for obtaining the raw material mixture is carried out by a solid-phase method or a liquid-phase method using a solvent, it is preferable to carry out a step of removing the solvent before the firing step, so that the firing step can be carried out efficiently. The method for removing the solvent is not particularly limited, but a method of evaporating the solvent is preferred, and a method of heating the raw material mixture is preferred. The heating temperature is preferably 80 to 200°C, more preferably 100 to 160°C, in order to reduce costs such as electricity costs for operating the equipment and ensure drying efficiency. From the viewpoint of operational efficiency, the heating time is preferably 1 to 48 hours, and more preferably 6 to 24 hours in order to completely evaporate the solvent. In the case of the liquid phase method, a suitable method is to obtain a raw material mixture by controlling the pH of the solution by adding a basic substance, etc., to precipitate salts of the metal elements and separating them as precipitates. The basic substance can be a carbonate or hydroxide salt of an alkali metal element.

[0032] When the mixing step is carried out by a solid-phase method or a liquid-phase method using a solvent, it is preferable to carry out a step of disintegrating the aggregated raw material mixture after the step of removing the solvent, so that the raw material mixture can be more thoroughly fired in the subsequent firing step. The method for crushing the raw material mixture is not particularly limited, but a sample mill, a roll mill, a hammer mill, a vibration mill, a jet mill, or the like can be used.

[0033] When the mixing step is carried out by a liquid phase method, it is preferable to carry out a crude firing step before the firing step. This makes it possible to remove carbon components and suppress side reactions caused by the carbon components and segregation of component metal elements. When the solvent removal step or the crushing step is carried out, it is preferable to carry out the crude firing step after these steps. The temperature at which the crude firing step is carried out is preferably 300 to 500°C in order to remove carbon components and prevent segregation of component metal elements, more preferably 350 to 500°C, and further preferably 400 to 500°C. The time for carrying out the crude firing step is preferably 1 to 24 hours from the viewpoint of operational efficiency, more preferably 4 to 24 hours, and further preferably 4 to 16 hours, in order to remove carbon components.

[0034] When the above-mentioned crude firing step is performed, it is preferable to perform a step of crushing the crude fired product after the crude firing step and before the firing step. The crushing can be performed using a sample mill, a roll mill, a hammer mill, a vibration mill, a jet mill, or the like.

[0035] The method for producing a composite material of the present invention includes a step of firing the raw material mixture obtained in the raw material mixing step at 800 to 1300°C. When the raw material compounds are mixed in a powder state in the raw material mixing step, the obtained raw material mixture can be fired at 800 to 1300°C as it is, but when the raw material compounds are mixed in a slurry state or in a solution dissolved in a solvent in the raw material mixing step, it is preferable to remove the solvent from the slurry or solution of the raw material mixture by the above method or the like and then fire at 800 to 1300°C. Note that the removal of the solvent here means that 90% or more of the solvent used in the raw material mixing step has been removed. Therefore, the firing step is preferably a step of firing the raw material mixture obtained in the raw material mixing step in a solid state at 800 to 1300°C. The solid state referred to here refers to powder, pellets, noodles, and other molded products.

[0036] The firing temperature in the firing step may be 800 to 1300°C, but is preferably 850 to 1300°C in order to obtain a composite material with high crystallinity. More preferably, it is 900 to 1280°C. In order to suppress destruction of the fine composite structure due to grain growth, it is even more preferably 900 to 1250°C. Particularly preferably, it is 900 to 1200°C, and most preferably, it is 900 to 1100°C. From the viewpoint of operational efficiency, the calcination time is preferably 1 to 24 hours, more preferably 1 to 18 hours, and even more preferably 2 to 12 hours in order to avoid the inclusion of any phase other than the above-mentioned electron conductive material and ion conductive material.

[0037] The method for producing a composite material of the present invention may include other steps as long as it includes a mixing step of mixing the above-mentioned raw materials to obtain a raw material mixture, and a step of firing the raw material mixture at 800 to 1300° C. Examples of other steps include a step of removing the solvent before the above-mentioned firing step, a step of pulverizing the material after the firing step, and a step of drying the material after the pulverizing step when the pulverizing step is performed in a wet state.

[0038] In the step of crushing the material after the firing step, it is desirable to crush the material finely from the viewpoint of suppressing peeling and cracking of the film in the electrode film preparation step, and it is preferable to perform wet crushing. As the solvent used in wet crushing, water, organic solvent, etc. can be used. The step of crushing the material is preferably performed until the D50 after crushing is 10 μm or less, more preferably 1 μm or less. In the case of wet grinding, a planetary ball mill, a bead mill, a vibration mill, a media-less grinder, etc. can be used. The media used preferably have a diameter of 0.1 to 5 mm in order to maintain the grinding efficiency and suppress the inclusion of impurities derived from the media. When a wet grinding step is carried out, the subsequent step of drying the material can be carried out by drying at 80 to 160°C.

[0039] 2. Composite material The present invention also relates to the following formula (1); X 1-p Sr p CoO 3-δ (1) (In the formula, X represents at least one element selected from La, Sm, and Gd, and 0 < p < 1. δ represents the amount of oxygen deficiency.) and an electronically conductive material represented by the following formula (2); Ce 1-q A q O 2-q / 2 (2) (In the formula, A represents at least one element selected from La, Sm, and Gd, and 0 < q < 1.) A composite material with an ion conductive material represented by, wherein the composite material is press-molded and fired to obtain a density of 4.5 to 6.5 g / cm 3 In a 4.5 μm × 6.0 μm field of view obtained by photographing a cross-section of a sintered body with an electron microscope, the ratio of the length of the interface where the electronically conductive material particles and the ion conductive material particles are in contact to the number of electronically conductive material particles (interface length / number of electronically conductive material particles) measured by the following method is greater than 0 μm and 13 μm or less. It is also a composite material characterized by this. <Method for measuring the length of the interface where the electronically conductive material particles and the ion conductive material particles are in contact> The backscattered electron image of the cross-section of the sintered body is divided into an ion conductive material phase, an electronically conductive material phase, and a pore phase by binarization by specifying the luminance range, and the perimeter of each phase is calculated and calculated by the following formula. (Length of the interface between the electronically conductive material phase and the ion conductive material phase) = (Perimeter of the electronically conductive material phase + Perimeter of the ion conductive material phase - Perimeter of the pore phase) / 2 <Method for measuring the number of electronically conductive material particles> The closed region of the electronically conductive material in the binarized region after the above binarization process is regarded as one particle, and the total number of them is counted as the number of electronically conductive material particles.

[0040] In solid oxide fuel cells, the lower the activation energy of the electrode reaction, the more the electrode resistance can be suppressed when the operating temperature of the cell is lowered. The present inventors have investigated whether there is a correlation between the activation energy of the electrode reaction of a composite material composed of an electronic conductive material represented by the above formula (1) and an ion conductive material represented by the above formula (2) and the shape of the material, and have found that there is a positive correlation between the ratio of the length of the interface where the electronic conductive material particles and the ion conductive material particles are in contact with each other to the number of electronic conductive material particles in a sintered compact of the composite material (interface length / number of electronic conductive material particles) and the activation energy of the electrode reaction calculated from the electrode resistance value of the composite material in a wide temperature range. It has generally been thought that the activation energy of the electrode reaction is lower when the length of the interface where the electronic conductive material particles and the ion conductive material particles are in contact is longer and the number of electronic conductive material particles is smaller from the viewpoint of reducing grain boundary resistance, so the correlation that the activation energy of the electrode reaction is lower as the value of the ratio is smaller is contrary to expectations. Based on this finding, the composite material of the present invention is a composite material in which an electronic conductive material represented by the above formula (1) and an ion conductive material represented by the above formula (2) are combined, and the composite material has a low activation energy of an electrode reaction.

[0041] In the composite material of the present invention, the above ratio (interface length / number of electron conductive material particles) may be greater than 0 μm and not greater than 13 μm, but from the viewpoint of reducing the activation energy in the electrode reaction, it is preferably not greater than 12 μm. More preferably, it is not greater than 11 μm, and most preferably, it is not greater than 10 μm. Also, it is preferably not less than 0.1 μm. More preferably, it is not less than 1.5 μm, and most preferably, it is not less than 3.0 μm. In the composite material of the present invention, the ratio of the number of particles of the electron conductive material to the total number of particles may be 10% or more, but from the viewpoint of reducing the activation energy in the electrode reaction, it is preferably 13% or more, more preferably 15% or more, and more preferably 50% or less, and more preferably 30% or less. The number of ion conductive material particles required to obtain the total particle number of the composite material can be obtained by treating each closed area of ​​the ion conductive material in the binarized area after the binarization process as one particle, and counting all of them to obtain the number of ion conductive material particles, similar to the method for measuring the number of electronically conductive material particles described above.

[0042] The composite material of the present invention can be produced by the above-mentioned method for producing a composite material of the present invention. The ratio of the number of particles of the electronic conductive material to the total number of particles and the ratio of (interface length / number of particles of the electronic conductive material) in the sintered body of the obtained composite material can be adjusted by the type of raw material used to prepare the precursor, the degree of dispersion of each metal element in the raw material mixture, and the firing temperature when obtaining the above-mentioned composite material.

[0043] The composite material of the present invention is a composite material of the electronic conductive material represented by the above formula (1) and the ion conductive material represented by the above formula (2), and the weight ratio of these electronic conductive material and ion conductive material is preferably 25 to 60% by weight, more preferably 35 to 60%, and further preferably 40 to 55% in order to increase the contact points between the electronic conductive material phase and the ion conductive material phase.

[0044] The composite material of the present invention has a low activation energy for the electrode reaction and can therefore be suitably used as an electrode for fuel cells, such as solid oxide fuel cells, which require a lower operating temperature. Such a fuel cell electrode, which is characterized by using the composite material of the present invention, also constitutes one aspect of the present invention. EXAMPLES

[0045] In order to explain the present invention in detail, specific examples are given below, but the present invention is not limited to these examples. Unless otherwise specified, "%" and "wt%" mean "weight % (mass %)". The measurement methods for each physical property are as follows.

[0046] Example 1 (1) Manufacturing of composite materials Samarium(III) carbonate hydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Sm2O3 equivalent purity: 46.8% by weight, hereafter the same) 58.00 g, strontium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.6% by weight, hereafter the same) 15.14 g, basic cobalt(II) carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Co3O4 equivalent purity: 60.3%, hereafter the same) 27.22 g, cerium carbonate ( III) 70.82 g of octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., CeO2 equivalent purity: 52.0%, hereinafter the same) was weighed out, put into 225.00 g of water and stirred to form a slurry, and the slurry was dispersed, pulverized and mixed for 300 minutes at a rotation speed of 180 rpm using a planetary ball mill (P-5 manufactured by Fritsch, hereinafter the same) with zirconia beads of 1 mm diameter as a pulverizing medium. The D50 of the slurry was measured with a laser diffraction / scattering type particle size distribution analyzer (LA-950 manufactured by Horiba, Ltd., hereinafter the same), and was found to be 0.10 μm. The measurement conditions are shown below. <Particle size distribution measurement conditions> Sample refractive index: 2.0 Particle shape: non-spherical Dispersion medium: 0.025% by weight sodium hexametaphosphate aqueous solution Solvent refractive index: 1.333 Transmittance (R): 85±5(%)

[0047] Next, the beads in the slurry treated as described above were removed using a sieve, and the slurry was dried in a dryer (DKN601 manufactured by Yamato Scientific Co., Ltd., hereinafter the same) set at a temperature of 150°C, and then crushed in a sample mill to obtain a composite material precursor as a powder. Next, the composite material precursor powder thus obtained was filled into an alumina crucible, and the crucible was placed in an electric furnace (BH-2K manufactured by ADVANTECH Co., Ltd., hereinafter the same) and fired in an air atmosphere at 1000°C for 4 hours. The fired product thus obtained was placed in water and stirred to form a slurry, and the slurry was then pulverized in a planetary ball mill at 180 rpm for 53 minutes using zirconia beads with a diameter of 1 mm as the pulverizing medium. The D50 of the slurry was measured using the above-mentioned laser diffraction / scattering particle size distribution analyzer, and was found to be 0.6 μm. Next, the beads in the slurry thus treated were removed using a sieve, and the slurry was dried in a dryer set at 150° C., and then crushed in a sample mill to obtain 50% by weight samarium strontium cobaltite (Sm 0.5 Sr 0.5 Chief of Staff 3-δ , hereafter abbreviated as SSC)-50 wt% samarium-doped ceria (Ce 0.8 Sm 0.2 O 1.9 A composite material of SDC (single-layered carbon black) was obtained as a powder. The X-ray diffraction pattern of this composite powder was measured, and it was confirmed that there was no crystal phase other than the strontium cobaltate perovskite-type oxide represented by formula (1) and the fluorite-type cerium oxide represented by formula (2). The conditions for measuring the X-ray diffraction pattern are shown below. <Conditions for measuring powder X-ray diffraction patterns> Optical system: Parallel beam optical system (long slit: PSA200 / resolution: 0.057°) Tube voltage: 50kV Current: 300mA Measurement method: Continuous scan Measurement range (2θ): 10°~60° Sampling width: 0.04° Scan speed: 5° / min The fact that the material was a composite material of an electronic conductive material and an ion conductive material was confirmed by confirming the composition of particles in a backscattered electron image taken with an electron microscope (JSM-7000F manufactured by JEOL Ltd., hereinafter the same) through point analysis using an energy dispersive X-ray analyzer mounted on the above electron microscope. <Conditions for taking backscattered electron images using an electron microscope> Accelerating voltage: 15.0 kV Magnification: 20,000x

[0048] (2) Evaluation of composite materials The activation energy of the electrode reaction of the composite material obtained in (1) above and the ratio of the length of the interface where the electronic conductive material particles and the ion conductive material particles are in contact with each other to the number of electronic conductive material particles in the sintered body of the composite material (interface length / number of electronic conductive material particles) were confirmed as follows. (2-1) Activation energy of electrode reactions in composite materials 2.24 g of the composite powder obtained in (1) above was mixed with 0.24 g of ethyl cellulose (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 45 cP) and 2.45 g of α-terpineol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 98.0%), and the mixture was kneaded for 15 minutes in a kneader (ARE-250 manufactured by Thinky Corporation) to obtain a slurry for an electrode. The electrode slurry was then 0.9 Gd 0.1 O 1.95 The slurry was applied to the sintered pellets in a size of 7 mm in diameter, and then placed in a dryer and dried at 110°C for 10 minutes. The electrode slurry was applied to the other side in the same manner, dried, and then placed in an electric furnace and held at 900°C for 2 hours to bake the electrode. 0.9 Gd 0.1 O 1.95 The sintered pellets were made using a 20 mm diameter carbide die. 0.9 Gd 0.1 O 1.95 The powder (1.3 g, manufactured by Solvay Specialchem ​​Japan) was biaxially press-molded at 100 MPa, then placed in an electric furnace and fired at 1400°C for 5 hours to obtain the powder. The electrode resistance per area was measured for the obtained electrode at 850°C, 800°C, 750°C, and 700°C in air by AC impedance spectroscopy (Solatron ModuLab XM), and the activation energy for the electrode reaction was calculated. -1 ) is calculated by multiplying the absolute value of the slope of the graph obtained by setting the axes under the conditions shown below by the gas constant (8.31 [J·K -1 mol -1]) was multiplied. Vertical axis: loge{1 / (electrode resistance per area)[Ω -1 m -2 ]} Horizontal axis: 1000 / (absolute temperature) [K -1 ] The electrode resistance is the difference between the two intercepts of the real part of the arc plotted as a Cole-Cole plot obtained by the AC impedance method and the resistance axis.

[0049] (2-2) (Interface length / number of electronic conductive material particles) of sintered composite material Using a carbide die with a diameter of 5 mm, 0.3 g of the composite material powder obtained in (1) above was biaxially press-molded at 100 MPa, and then placed in an electric furnace and sintered at 1000°C for 2 hours to obtain a sintered body. The sintered body was weighed, its dimensions were measured with calipers, and the density was calculated by dividing the weight of the sintered body by the volume calculated from the dimensions (5.0 g / cm3). 3 The cross section of the sintered body was smoothed using a cross section smoothing device (Cross Section Polisher SM-09010 manufactured by JEOL Ltd.), and a backscattered electron image of the cross section was obtained using an electron microscope. Image analysis software (WinROOF2015 manufactured by Mitani Shoji Co., Ltd., hereinafter the same) was used to evaluate the ratio of the length of the interface where the electron conductive material particles and the ion conductive material particles are in contact with each other to the number of electron conductive material particles (interface length / number of electron conductive material particles). The shooting conditions for the backscattered electron image and the image analysis method are shown below. <Image analysis> All image analyses were performed using the above-mentioned image analysis software in the following procedure. First, the backscattered electron image (field of view: 4.5 μm × 6.0 μm) obtained under the above conditions was read into the image analysis software and the scale was calibrated by using the "manual calibration" function to align the line with the 1 μm scale bar written in the analysis conditions column below the backscattered electron image and inputting 1 μm as the actual size value. Next, the entire area excluding the analysis condition column below the backscattered electron image was selected using a rectangular ROI, and the selected area was cut out to extract the image area related to the particles (original image). Next, in order to enhance the contrast of the backscattered electron image above, the “Brightness / Contrast” function was used and the contrast value was changed to 55 (contrast enhancement). Next, sorting and quantization were performed to average the brightness. Sorting was performed using the "Filter" function, with sorting checked and a filter size of 9 x 9 pixels, four times in total (output order 1st: 21, 2nd: 61, 3rd: 21, 4th: 61). After sorting, all areas except for the unprocessed area 4 pixels inside the image edge were selected using a rectangular ROI, and the selected area was cut out (sorting). Next, the brightness quantization in the "Lookup table conversion" function was checked, and the quantization number was set to 32, thereby changing the interval width of the brightness histogram to 8 times. The histograms before and after quantization of the material in Example 1 are shown in Figure 1 (brightness quantization). Based on the brightness histogram in the image after the above processing, binarization processing was performed by specifying the brightness range. The histogram is attributed to a vacancy phase, an electronic conductive material phase, and an ion conductive material phase in order from the low brightness side. The boundary between the vacancy phase and the electronic conductive material phase is the brightness at which a peak having a frequency of 0.30 times or more appears when counting from the first peak on the low brightness side to the high brightness side, based on the frequency of the first peak (brightness division: 7 to 14) on the low brightness side, and the brightness is attributed to the electronic conductive material phase. Note that the peak refers to the frequency bar of each brightness division of the brightness histogram, and the frequency is the number obtained by adding up the number of each pixel within the ROI range for each brightness division. The boundary between the electronic conductive material phase and the ion conductive material phase is the brightness at which the area ratio of the electronic conductive material phase exceeds 50% and is closest to 50% with respect to the total area of ​​the electronic conductive material phase and the ion conductive material phase. For the material of Example 1, the brightness value, frequency, first peak ratio on the low brightness side, and the area ratio of the electronic conductive material phase to the total area of ​​the electronic conductive material phase and the ion conductive material phase are shown in FIG. 2. In FIG. 2, the boundary between the vacancy phase and the electronic conductive material phase, and the boundary between the electronic conductive material phase and the ion conductive material phase are shown by dotted lines. The frequency of the brightness histogram can be confirmed from the histogram in the measurement tool of the analysis software. A histogram was obtained by selecting within the ROI range, setting the histogram series to 256, the class division to equal (lower limit: 0, upper limit: 255), and the graph vertical axis to frequency, and replacing the series 1 to 256 of the histogram with brightness 0 to 255 to obtain a brightness histogram. Brightness n corresponds to series n-1, and n is an integer from 0 to 255. The area ratio of the electronic conductive material phase was obtained by calculating the ratio of the cumulative frequency of luminance attributable to the electronic conductive material phase to the cumulative frequency of luminance attributable to the electronic conductive material phase or the ion conductive material phase as a percentage. The cumulative frequency of luminance attributable to the electronic conductive material phase or the ion conductive material phase was obtained by subtracting the cumulative frequency of luminance attributable to the vacancy phase described above from the cumulative frequency of the entire luminance (binarization). After binarization, the perimeter of the binarized region of each phase was calculated by selecting "Perimeter including holes" from the "Shape Features" function. "Perimeter including holes" refers to the length of the boundary between the binarized region and the non-binarized region that exists inside and outside the binarized region. The net perimeter was calculated by subtracting the binarized region on the edge of the image from the calculated perimeter. Since the interface of each phase is in contact with one or both of the other two phases, the length of the interface between the electronically conductive material phase and the ionically conductive material phase was calculated using the following formula. (Interface length between electronic conductive material phase and ionic conductive material phase) = (Perimeter length of electronic conductive material phase + Perimeter length of ionic conductive material phase - Perimeter length of vacancy phase) / 2 Images at each of the above stages are shown in Figures 3-1 to 3-5, and images of the upper left regions of Figures 3-1 to 3-5 are enlarged in Figures 4-1 to 4-5. In Figures 3-1 to 3-4 and 4-1 to 4-4, the dark areas are electronic conductive material, the light areas are ion conductive material, and the black areas are pores, while in Figures 3-5 and 4-5, the white areas are electronic conductive material, the shaded areas are ion conductive material, and the black areas are pores. The values ​​of (interface length / number of particles of electronic conductive material) obtained from the image analysis are shown in Table 1. Furthermore, the correlation between the activation energy of the electrode reaction of the composite material and the value of (interface length / number of particles of electronic conductive material) is shown in FIG. The number of particles mentioned above is the number of particles counted, with each closed region in the binarized region regarded as one particle, and is synonymous with the number of independent binarized regions mentioned above. In addition, it can be confirmed that the histograms assigned at the above boundaries are electronic conductive materials and ionic electronic conductive materials by overlaying the backscattered electron image on an element mapping image obtained by energy dispersive X-ray analysis (EDS) that can be obtained by observation with a scanning electron microscope.

[0050] Example 2 43.97g of samarium (III) carbonate hydrate, 11.49g of strontium carbonate, 20.87g of basic cobalt (II) carbonate, 53.71g of cerium (III) carbonate octahydrate, 105.80g of citric acid monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.5%), and 31.16g of DL-malic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.0%) were weighed, and only the metal salt raw material was put into water and stirred to form a slurry, and then citric acid and malic acid were put in order and stirred to obtain an aqueous solution of metal salt. The aqueous solution was transferred to an evaporating dish, dried in a dryer at 150 ° C. for 24 hours, and then crushed with a sample mill to obtain a precursor. Next, the precursor was calcined in an electric furnace at 500°C for 12 hours to remove carbon components, and then the calcined product was crushed in a mortar, transferred to an alumina crucible, and calcined in an electric furnace at 1000°C for 4 hours to obtain a calcined product (composite material). The fired product thus obtained was put into water and stirred to form a slurry, and the slurry was then pulverized in a planetary ball mill using zirconia beads with a diameter of 1 mm as a pulverizing medium at a rotation speed of 180 rpm until the D50 of the slurry became 0.6 μm (pulverization time: 50 minutes), to obtain a composite material of 50 wt% SSC-50 wt% SDC. The pulverized composite material was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0051] Example 3 43.78g of samarium (III) carbonate hydrate, 11.49g of strontium carbonate, 53.55g of cerium (III) carbonate octahydrate, 21.31g of citric acid monohydrate, and 81.59g of DL-malic acid were weighed out, and only the metal salt raw materials were put into water and stirred to form a slurry, and then citric acid and malic acid were added in order and stirred to obtain an aqueous solution of metal salts. 12.45g of tricobalt tetroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%, the same applies below) was weighed out into the aqueous solution, and the solution was dispersed with a dispersing machine (TK homomixer manufactured by Primix Corporation) at 5000 rpm for 30 minutes to obtain a slurry. The slurry was transferred to an evaporating dish and dried in a dryer at 150° C. for 24 hours. Then, it was crushed in a sample mill to obtain a precursor. The fired product thus obtained was put into water and stirred to form a slurry, and the slurry was then ground in a planetary ball mill using zirconia beads with a diameter of 1 mm as a grinding medium at a rotation speed of 180 rpm until the slurry had a D50 of 0.5 μm (grinding time: 50 minutes), to obtain a composite material of 50 wt% SSC-50 wt% SDC. The ground composite material was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0052] Example 4 43.97 g of samarium (III) carbonate hydrate, 11.49 g of strontium carbonate, 20.87 g of basic cobalt (II) carbonate, 30.03 g of cerium (IV) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 93.0%, the same applies below), 4.26 g of citric acid monohydrate, and 16.32 g of DL-malic acid were weighed out, and a fired product (composite material) was obtained in the same manner as in Example 3. The fired product thus obtained was put into water and stirred to form a slurry, and the slurry was then pulverized in a planetary ball mill using zirconia beads with a diameter of 1 mm as a pulverizing medium at a rotation speed of 180 rpm until the D50 of the slurry became 0.4 μm (pulverization time: 60 minutes), to obtain a composite material of 50 wt% SSC-50 wt% SDC. The pulverized composite material was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0053] Example 5 Gadolinium (III) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.9% by weight, hereinafter the same), 29.91 g, strontium carbonate, 16.00 g, basic cobalt (II) carbonate, 28.73 g, and cerium (III) carbonate octahydrate, 75.37 g were weighed out, put into 225.00 g of water, stirred, and slurried, and the slurry was dispersed, pulverized, and mixed at a rotation speed of 180 rpm for 120 minutes using zirconia beads with a diameter of 1 mm as a pulverizing medium in a planetary ball mill. The D50 of the slurry was measured and found to be 0.11 μm. Next, the beads in the slurry were removed using a sieve, and the slurry was dried in a dryer set at a temperature of 150°C, and then crushed in a sample mill (SK-M10 manufactured by Kyoritsu Kiko Co., Ltd.) to obtain a composite material precursor powder. Next, the composite material precursor powder thus obtained was filled into an alumina crucible, and the crucible was placed in an electric furnace and fired in the air at 1100° C. for 4 hours. The fired product thus obtained was placed in water and stirred to form a slurry, and the slurry was then pulverized in a planetary ball mill at a rotation speed of 180 rpm for 90 minutes using zirconia beads having a diameter of 1 mm as a pulverizing medium. The D50 of the slurry was measured and found to be 0.55 μm. Next, the beads in the slurry were removed using a sieve, and the slurry was dried in a dryer set at a temperature of 150° C., and then crushed in a sample mill to obtain 50% by weight gadolinium strontium cobaltite (Gd 0.5 Sr 0.5 Chief of Staff 3-δ , hereafter abbreviated as GSC)-50 wt% gadolinium-doped ceria (Ce 0.8 Gd 0.2 O 1.9 A composite powder of GDC (Gel-Derived Carbon Dioxide) was obtained. The composite material powder after pulverization was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0054] Example 6 27.56g of lanthanum(III) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.9% by weight, hereinafter the same), 16.51g of strontium carbonate, 29.65g of basic cobalt(II) carbonate, and 76.28g of cerium(III) carbonate octahydrate were weighed out, put into 225.00g of water, stirred, and slurried, and the slurry was dispersed, pulverized, and mixed at 180 rpm for 330 minutes using zirconia beads with a diameter of 1 mm as a pulverizing medium in a planetary ball mill. The D50 of the slurry was measured and found to be 0.12 μm. Next, the beads in the slurry were removed using a sieve, and the slurry was dried in a dryer set at a temperature of 150°C, and then crushed in a sample mill (SK-M10 manufactured by Kyoritsu Kiko Co., Ltd.) to obtain a composite material precursor powder. Next, the composite material precursor powder thus obtained was filled into an alumina crucible, and the crucible was placed in an electric furnace and fired in the air at 1250° C. for 4 hours. The fired product thus obtained was placed in water and stirred to form a slurry, and the slurry was then pulverized in a planetary ball mill at 180 rpm for 90 minutes using zirconia beads having a diameter of 1 mm as a pulverizing medium. The D50 of the slurry was measured and found to be 0.53 μm. Next, the beads in the slurry were removed using a sieve, and the slurry was dried in a dryer set at a temperature of 150° C., and then crushed in a sample mill to obtain 50% by weight lanthanum strontium cobaltite (La 0.5 Sr 0.5 Chief of Staff 3-δ , hereafter abbreviated as LSC)-50 wt% lanthanum doped ceria (Ce 0.8 La 0.2 O 1.9 A composite powder of LDC (Lysine-Derived Carbon Dioxide) was obtained. The composite material powder after pulverization was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0055] Comparative Example 1 41.64 g of samarium (III) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.2 wt%), 23.05 g of strontium carbonate, 24.99 g of tricobalt tetroxide, and 60.32 g of cerium (IV) oxide were weighed, and a composite material precursor was obtained as a powder in the same manner as in Example 1. The calcined product obtained under the same calcination conditions as in Example 1 was put into water and stirred to form a slurry, and the slurry was then ground using zirconia beads with a diameter of 1 mm as a grinding medium using a planetary ball mill at a rotation speed of 180 rpm until the D50 of the slurry became 0.6 μm (grinding time: 47 minutes), and a composite material of 50 wt% SSC-50 wt% SDC was obtained. The obtained composite material was subjected to evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0056] [Table 1]

[0057] As shown in Table 1 and FIG. 5, a positive correlation was confirmed between the (interface length / number of particles of electronic conductive material) of the sintered body of the composite material and the activation energy of the electrode reaction of the composite material calculated from the electrical resistance value in the temperature range of 700 to 850 ° C., and it was confirmed that the composite material having a value of (interface length / number of particles of electronic conductive material) of 13 μm or less has a low electrode resistance value in a wide temperature range including a low temperature range below 800 ° C. and a low activation energy of the electrode reaction. In addition, it was confirmed that the composite materials obtained in Examples 1 to 6 have a higher proportion of the number of particles of the electronic conductive material than the composite material obtained in Comparative Example 1, and that the composite material having this value of 10% or more has a low electrode resistance value in a wide temperature range including a low temperature range below 800 ° C. and a low activation energy of the electrode reaction. It was also confirmed that the manufacturing method of the present invention can easily manufacture a composite material having a low electrode resistance value and a low activation energy of the electrode reaction in a wide temperature range including a low temperature range below 800 ° C. without imposing a heavy burden on the environment.

Claims

1. The following formula (1): X 1-p Sr p CoO 3-δ (1) (wherein X represents at least one element selected from La, Sm, and Gd, and 0<p<1; and δ represents the amount of oxygen deficiency), and an electron conductive material represented by the following formula (2); Yes 1-q A q O 2-q/2 (2) (wherein A represents at least one element selected from La, Sm, and Gd, and 0<q<1), The production method includes a mixing step of mixing raw materials including a compound containing a metal element constituting an electronic conductive material and an ion conductive material to obtain a raw material mixture; and introducing the raw material mixture into a heating device and firing it at 800 to 1300°C. The Sr-containing compound contained in the raw material is a carbonate, and at least one of the compounds containing a metal element other than Sr is a carbonate. A method for producing a composite material comprising the steps of:

2. 2. The method for producing a composite material according to claim 1, wherein the Co-containing compound among the compounds containing a metal element other than Sr is a carbonate.

3. 3. The method for producing a composite material according to claim 1, wherein the mixing step is a step of mixing a raw material containing at least one carbonate with a compound containing a metal element other than Sr in a powder or slurry state.

4. 3. The method for producing a composite material according to claim 1, wherein the mixing step is a step of dissolving raw materials including at least a carbonate containing an X element in formula (1) or an A element in formula (2) and a carbonate containing Ce or Co in a solvent and mixing the raw materials.

5. The following formula (1): X 1-p Sr p CoO 3-δ (1) (wherein X represents at least one element selected from La, Sm, and Gd, and 0<p<1; and δ represents the amount of oxygen deficiency), and an electron conductive material represented by the following formula (2); Yes 1-q A q O 2-q/2 (2) (wherein A represents at least one element selected from La, Sm, and Gd, and 0<q<1), The composite material is press molded and sintered to obtain a density of 4.5 to 6.5 g / cm 3 a ratio of the length of an interface between electron conductive material particles and ion conductive material particles to the number of electron conductive material particles (interface length / number of electron conductive material particles) measured by the following method in a field of view of 4.5 μm × 6.0 μm obtained by photographing a cross section of the sintered body of the above-mentioned composition using an electron microscope is greater than 0 μm and is not greater than 13 μm. <Method for measuring the length of the interface between particles of an electronic conductive material and particles of an ion conductive material> The backscattered electron image of the cross section of the sintered body is divided into an ion-conductive material phase, an electronic-conductive material phase, and a void phase by binarization according to a specified brightness range, and the perimeter of each phase is calculated according to the following formula. (Length of interface between electronic conductive material phase and ion conductive material phase)=(Perimeter of electronic conductive material phase+Perimeter of ion conductive material phase−Perimeter of vacancy phase) / 2 <Method for measuring the number of electron conductive material particles> A closed region in the binarized region after the binarization process is regarded as one particle, and the number of all the closed regions is regarded as the number of electron conductive material particles.

6. 6. The composite material according to claim 5, wherein the ratio of the number of the electron conductive material particles to the total number of the electron conductive material particles and the ion conductive material particles is 10% or more.

7. 7. An electrode for a fuel cell, comprising the composite material according to claim 5 or 6.

Citation Information

Patent Citations

  • Composite particle powder, electrode material for solid oxide cells, and electrode for solid oxide cells using same

    WO2018084279A1